Investigation of Benzoic Acid Adsorption on to ODTMA-Bentonite by Response Surface Optimization - H. Kapucu; N. Yildiz; R. Gönülşen; A. Ç Çalimli (Adsorption Science & Technology)
The adsorption of benzoic acid on to a modified bentonite (ODTMA-bentonite) was studied. ODTMA-bentonite was synthesized by the incorporation of a quaternary ammonium surfactant (octadecyltrimethylammonium bromide) on to Ç ankiri sodium bentonite (Ç Na-B) with a cation-exchange capacity of 85 mequiv/100 g clay. A 2 4 full factorial central composite experimental design followed by multi-stage Monte-Carlo optimization was used in designing the experiments and analyzing the results. This procedure limited the number of actual experiments performed whilst allowing for possible interactions between the four parameters studied. These parameters were temperature (20–40°C), agitation rate (30–170 rpm), the amount of organobentonite used (0.1–1.5 g) and the initial benzoic acid concentration (40–200 mg/l). Of these parameters, the amount of organobentonite and the temperature had significant effects in comparison with the agitation rate and initial benzoic acid concentration. To effect the maximum adsorption of benzoic acid on to ODTMA-bentonite, the optimum values for the tested variables over the selected ranges were as follows: initial concentration of benzoic acid = 200 mg/l, agitation rate = 170 rpm, amount of organobentonite = 1.5 g and temperature = 40°C. The coefficient of determination (R 2 ) for the model employed was 0.99343 with a probability value of 9.44 × 10 −14 (p-value < 0.01). This p-value indicates a very high significance for the regression model. The maximum adsorbed concentration of benzoic acid predicted by the equation (169.05 mg/l) agreed well with the value (163 mg/l) obtained from the experimental data measured under optimum conditions.